Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Konsumen Louis Cafe Depok - Bunga Herlambang; Anjar Dwi Astono (UNIVERSITAS KALBIS, 2023)
The purpose of this research, to determine the effect of service quality and product qualityon customer satisfaction at Louis Cafe Depok. This research was conducted from February to June2022 with the amount of data from the research instrument via Google Form as many as 110respondents. The sampling technique in this study used non-random sampling with purposivesampling method. The result of this study indicates that there is no symptom of heteroscedasticity inthe service quality and product quality variable so linear regression is effective to show the resultthat service quality has a significant effect on customer satisfaction, product quality has a significanteffect on customer satisfaction, service quality and product quality has a significant effect oncustomer satisfaction.